Techniques in teaching vocabulary (Teaching Techniques in English as a Second Language) - Allen V. F.; Campbell R. N.; Rutherford W. E. (Hong Kong Oxford University Press, 1983)
This book provides a sound basis for teaching vocabulary and answers such questions as: Which English words students need to learn most? Why some words are easier to learn than others.
Keywords: 811.111